Integration of Islamic Marketing and Halal Business: A Systematic Review of Trends, Challenges, and Value Frameworks - Warto Warto (Journal of Islamic Economics (JoIE), 2026)
Introduction: The growth of the global halal industry requires a holistic integration between operational halal compliance and the ethical principles of Islamic Marketing to ensure product integrity, particularly in Indonesia as the world’s largest Muslim market. This study analyzes the conceptual synergy and the implementation of this integration. Research Method: We employed a Systematic Literature Review (SLR) using an adapted PRISMA protocol. Studies from Scopus and Sinta 1–3 (2017–2025) were analyzed thematically and narratively to synthesize the findings. Results: Effective integration is achieved through the Muslim Customer Perceived Value (MCPV) Halal framework, in which spiritual and ethical value dimensions (such as employee behavior and the shopping environment) enhance consumer trust and purchase intention beyond the fulfillment of legal certification requirements. Structural challenges include weaknesses in supply chain traceability and fragmented standards amid rapid digitalization. Conclusion: The integration of Halal Business and Islamic Marketing is essential for sustainable competitiveness. Required strategies include harmonizing global standards, advancing technological innovation for value chain transparency, and strengthening halal literacy.